PHYSICAL EDUCATION SCHOOL OF EDUCATION LEARNING (Fiep Bulletin - online, 2013)
Believing that needs to build a humanistic educational practice, conscious, guided by reflection, by critics and by building a shared knowledge are increasingly evident if we think in overcoming apriorisms determinants of educational activity developed in physical education classes, we aim with this, discuss with bibliographic procedure, the principles and core values ??Education and Physical Education, philosophy understood the real meaning of teaching and learning with hope and love.
Keywords: Physical Education; Teaching and Learning; Philosophy